Características Clínicas del Síndrome de Guillain-Barré en Relación a Chikungunya Y Zika: Revisión Sistemática. (2018)
In the last five years, there have been several cases of zika and chikungunya infections in the world, simultaneous with the increase in cases of Guillain-Barre syndrome, which have shown a potential causal relationship that is still not entirely clear. Objective: To describe the main clinical manifestations of Guillain-Barre syndrome in relation to chikungunya and zika, according to scientific literature. Methods: The databases PubMed and ScienceDirect were used to perform the search for the period 2014-2016 using with the keywords: zika, chikungunya and Guillain-Barre Syndrome; articles in English and Spanish were included. Results: 35 articles were found, one for the year 2014, two for 2015 and 32 for 2016. Conclusion: Variations in clinical characteristics and the increased incidence of GBS in the presence of zika and chikungunya, highlight the need to monitor these infections and perform analytic studies to determine the association between arboviruses and different neurological alterations. © 2018 Fundacion para la difusion neurologica en Ecuador - FUNDINE. All rights reserved.